2004
DOI: 10.1136/jcp.2004.017434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ATM, p53, and the MRE11–Rad50–NBS1 complex in myoepithelial cells from benign and malignant proliferations of the breast

Abstract: Aims: To analyse the expression of proteins involved in DNA double strand break detection and repair in the luminal and myoepithelial compartments of benign breast lesions and malignant breast tumours with myoepithelial differentiation. Methods: Expression of the ataxia telangiectasia (ATM) and p53 proteins was immunohistochemically evaluated in 18 benign and malignant myoepithelial tumours of the breast. Fifteen benign breast lesions with prominent myoepithelial compartment were also evaluated for these prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
(12 reference statements)
0
17
1
1
Order By: Relevance
“…Hsp 27 has also been shown to have an anti-apoptotic role [34]. It can increase cell survival in response to apoptotic stimuli, activate protein kinase B, an apoptotic inhibitor [41,42]. In the present study no significant differences were found for BRCA1, ATM and BARD1 immunoreactivity between normal breast from cancer-containing breasts and non-cancerous breasts.…”
Section: Discussioncontrasting
confidence: 51%
“…Hsp 27 has also been shown to have an anti-apoptotic role [34]. It can increase cell survival in response to apoptotic stimuli, activate protein kinase B, an apoptotic inhibitor [41,42]. In the present study no significant differences were found for BRCA1, ATM and BARD1 immunoreactivity between normal breast from cancer-containing breasts and non-cancerous breasts.…”
Section: Discussioncontrasting
confidence: 51%
“…Allelic imbalance and microsatellite instability have also been described in AME 65. Expression of ATM, p53 and the MRE11-Rad50-NBS1 complex has been detected in myoepithelial cells from both benign and malignant proliferations of the breast and is not specific for AME 66. There is one case report of AME arising in association with neurofibromatosis but there is no other association with familial tumour syndromes 67.…”
Section: Molecular and Cytogenetic Features Of Amementioning
confidence: 99%
“…Recently, Angele and coworkers [61] found that human luminal and myoepithelial cells differ in their DNA repair capacity, and this may contribute to the lower rate of transformation in myoepithelial cells. Additionally, when they do undergo transformation, they usually form benign or low-grade neoplasms.…”
Section: Myoepithelial Cells Act In Tumor Suppressionmentioning
confidence: 99%